Optimizing the machinability of inconel 718 in the rotary abrasive water jet cutting process - W.Mohamad, W Noor Fatihah (2024)
The Abrasive Waterjet (AWJ) process is a cutting-edge technique utilized in modern machining for working with challenging materials. Leveraging its erosive effect, this method enables the precise machining of hard and brittle engineering materials. The incorporation of hard abrasive particles into the water jet facilitates a robust cutting process. Notably, the absence of thermal effects during AWJ operations eliminates concerns related to distortion, microstructure changes, and mechanical softening issues. Currently, AWJ applications are predominantly limited to cylindrical materials, particularly in the machining of Inconel 718. This study aims to assess the process parameters involved in cutting Inconel 718 using Abrasive Waterjet Turning (AWJT). Employing a Design of Experiments (DOE) approach, specifically the Box-Behken Design (BBD) with five center-point designs, the study explores rotational speeds of 60 and 90 rpm, feeds of 1.0 and 3.0 mm/min, and cutting depths of 0.1 and 0.5 mm. Parametric study data is analyzed using ANOVA. Surface roughness evaluation involves assessing 10 machining paths based on conventional turning operations. Surface conditions are characterized through elemental analysis and surface morphology. From the experimental result, a predictive model for the surface roughness within the experimental ranges was develop, highlighting the depth of cut and feed rate as the most influential parameters. Notably, a minimum surface roughness range of 2.09–2.61 µm, falling within the N7 grade is observed. Lower feed rates result in reduced striation, and optimal surface roughness is achieved with high rotational speed, low feed, and low cutting depth. Comparisons with traditional machining reveal a surface finish comparable to the turning process. After multi-objective parameter optimization targeting surface roughness, dimensional accuracy, and roundness, a 0.14 - 0.27% improvement in surface roughness is achieved. Microstructure analysis confirms the absence of deformation, indicating no alterations at the subsurface level. One-factor effect plots illustrate that enhancing the barrel shape and implementing a clockwise cutting direction result in improved surface texture with nearly imperceptible striations. This research underscores the viability of AWJT as a credible alternative to turning processes, particularly for machining hard materials.